Fibronectin type III and intracellular domains of Toll-like receptor 4 interactor with leucine-rich repeats (Tril) are required for developmental signaling - Kim, Hyung-Seok (Mol Biol Cell, 2018)
Toll-like receptor 4 interactor with leucine-rich repeats (Tril) functions as a coreceptor for Toll-like receptors (Tlrs) to mediate innate immune responses in adults. In embryos, Tril signals to promote degradation of the Bmp inhibitor, Smad7, to allow for blood formation. It is not known whether this function requires, or is independent of, Tlrs. In the current studies, we performed a structure–function analysis, which indicated that the fibronectin type III (FN) domain and the intracellular domain of Tril are required to trigger Smad7 degradation in Xenopus embryos. Furthermore, we found evidence suggesting that a Tril deletion mutant lacking the FN domain (Tril∆FN) can dominantly inhibit signaling by endogenous Tril when overexpressed. This finding raises the possibility that the FN domain functions to bind endogenous Tril ligands. We also show that Tril cycles between the cell surface and endosomes and that the Tril extracellular domain, as well as cadherin based cell–cell adhesion, are required for cell surface retention, while the intracellular domain is required for internalization in Xenopus ectodermal explants. Using a CHO cell aggregation assay, we show that, unlike other transmembrane proteins that contain leucine-rich repeats, Tril is not sufficient to mediate homophilic adhesion.